Notes: (3) Local Manufacture of Neolithic Pottery - Scott, W Lindsay; Phemister, James (Proceedings of the Society of Antiquaries of Scotland, 1942)
The discovery at the Neolithic occupation site of Bilean an Tighe, North Uist, of kilns in which pottery had been manufactured on a considerable scale and over a substantial period of time was reported in an earlier article. The similarity of the latest products of these kilns to pottery of the Unstan bowl type from Orkney, and particularly to a bowl from Rousay, suggested the possibility that the factory might have worked to some degree for export, and this possibility was tested by petrological examination of sherds from North Uist and Orkney sites. The evidence for local manufacture was in each case conclusive. The possibility of a Neolithic trade in pottery is naturally not excluded by the negative evidence of fourteen sherds, but it is rendered less likely.